Osteoarthritis Was Associated With a Faster Decline in Hippocampal Volumes in Cognitively Normal Older People - Li, Xiang; Tong, Qiaowen; Gao, Jianqing; Liu, Cailong; , Alzheimer’s Disease Neuroimaging Initiative; Liu, Yangbo (Frontiers in Aging Neuroscience, 2020)
Objective: To examine whether osteoarthritis (OA) is associated with change in adjusted hippocampal volumes (HpVR: hippocampal/intracranial volume ×103) over time among cognitively normal older people. Methods: We examined the cross-sectional and longitudinal associations of OA with HpVR among individuals with normal cognition (NC) from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) study. At baseline, a total of 372 individuals with NC was included. Results: In the cross-sectional analyses of baseline data, we did not find a significant relationship between OA and HpVR among individuals with NC. However, in the longitudinal analyses, OA was significantly associated with change in HpVR over time among individuals with NC. Specifically, compared with individuals without OA, those with OA showed a faster decline in HpVR over time when controlling other potential confounders, including age, educational attainment, gender, and APOE4 genotype. Conclusion: OA status was significantly associated with change in HpVR over time among individuals with NC.